Effectiveness of Abdominal Massage on Reducing Constipation in Patients with Diabetes Mellitus - Nurul Khairani; Hilman Syarif; Asniar Asniar (Rifa'Institute, 2026)
Introduction: Constipation is a common gastrointestinal complication in patients with diabetes mellitus and may reduce quality of life. Abdominal massage is a safe non-pharmacological nursing intervention that may improve bowel motility. Objective: This study evaluated the effectiveness of abdominal massage in reducing constipation among hospitalized patients with diabetes mellitus. Method: A quasi-experimental pretest-posttest control group design was used. Seventy participants were selected through purposive sampling and assigned to intervention and control groups of 35 each. The intervention group received a 15-minute abdominal massage once daily for three consecutive days, while the control group received routine care. Constipation severity was measured using the Constipation Scoring System. Data were analyzed using Wilcoxon signed-rank and Mann-Whitney tests. Result and Discussion: Baseline constipation scores did not differ significantly between groups. After intervention, the median score in the intervention group decreased from 17.00 to 10.00, whereas the control group remained at 17.00. The posttest difference between groups was significant. The improvement may reflect stimulation of parasympathetic activity, the gastrocolic reflex, and colonic motility. Conclusions: Abdominal massage effectively reduced constipation severity and may be integrated into routine nursing care and discharge planning